Studi Literatur; Analisis Kadar Logam Berat Pada Susu Kental Manis Kemasan Kaleng - Cukri Rahma; Itza mulyani; Safrida S (Jurnal Teknologi Pengolahan Pertanian, 2021)
Research has been carried out on the analysis of heavy metal content in canned sweetened condensed milk. This research aims to determine whether the levels of heavy metals in canned sweetened condensed milk have met the heavy metal quality standards set by BPOM regulations No.23:2017 and SNI-7387:2009. This study uses a literature review method with data collection and screening that has inclusion and exclusion criteria. The results obtained were the levels of heavy metals identified in canned sweetened condensed milk of 76.19% from 21 samples which included Pb 66.66%, Sn metal 33.33% and cadmium metal 19.04%. From the identified data, 85.71% Pb metal and 14.28% Sn metal did not meet the quality standards set by BPOM No.23:2017 and SNI-7387:2009.